Why Did They Switch? How Will They Come Back? - Sehirli, Mustafa; Fidan, Yahya; Cengiz, Hakan (Journal of Marketing Development and Competitiveness, 2018)
This study aims to understand why customers switch their service providers and to investigate the relationship between the customers’ reasons of switching and their intentions to come back (repurchase). First of all, an extensive literature review was performed on the topic of ‘’switching’’, on which not much of academic research has been conducted previously, and automotive industry was selected as the field of study as a result of its high sensitivity to the customer defections. The data was obtained by the telephone surveys made with 1902 customers, all who have switched their authorized service providers to unauthorized ones. Thus, the results were obtained according to the actual behaviors of switching, not to the intentions or attitudes. Within the frame of a model containing nine independent variables, the reasons of the customers for switching, and the relationships between their reasons of switching and intentions to repurchase were examined. Variables that have been proven to influence the customers’ switching behaviors and their intentions of repurchasing are service quality, customer satisfaction, commitment, value, attitudes toward switching, subjective norms, switching costs, variety seeking and alternative attractiveness. However, the effects of only four of these variables (customer satisfaction, alternative attractiveness, switching costs and attitudes toward switching) were regarded as truly meaningful. The most effective variable on the customers’ intentions for coming back is accepted to be the satisfaction. The final outcome of the research is to produce useful knowledge for the academicians and managers to understand the underlying factors of the switching behaviors of the customers and to learn how to manage them in today’s age of the customer.